Recuperação estrutural de blocos de fundação afetados pela reação álcali-agregado: a experiência do Recife - Gomes, Eduardo Alves de Oliveira (2008)
The first engineering works reported as being affected by Alkali-Aggregate Reaction (AAR) were pavements and bridges in the state of California - USA, in the 1920's. This diagnosis was proposed by Stanton, T.E., in 1940. From then on, many studies had been presented, supporting that hypothesis. From 1940 to nowadays many other countries, including Brazil had been diagnosing hundreds of cases of AAR in many different types of engineering works, mainly in dams. In Recife, Pernambuco, from the year 2000, many occurrences have been identified as AAR in pile caps. Initially they were observed in the basis of industrial cooling towers and in the pile caps of the Pina Bridge. In 2004, occurred in the neighbor city of Jaboatao the rupture of the Areia Branca Building, a 12 storey, 27 yearold, concrete construction, caused by constructive imperfections in the foundation of the columns. Many people that live in buildings worried much about this fact and asked technical inspections in the foundations. About 30 buildings presented various cracks and the cause is attributed to AAR. Because of the absence of registration of similar cases in the international literature and because the theoretical modelling of the problem is not yet satisfactorily solved, the structural engineers have been presenting intuitive solutions. In this paper four examples of solutions for structural repair of pile caps are showed, using in all of them common procedures, like: cleaning and fulfilling the cracks, addition of steel bars and covering the pile caps with a concrete layer in all surfaces. At the end it is talked about the need to increase the pile caps structural analysis, to verify if the AAR is the only responsible for the fissures in the pile caps, or if there are other associated pathologies